INCENTIVOS FISCALES, CRECIMIENTO EMPRESARIAL Y ESTRUCTURA DE CAPITAL - Blásquez Santana, Félix (2005)
The analysis of the managerial growth and its explanatory factors, they adopt a role protagonist and current in the process of globalization in the one that is the world economy. In this respect, the present work tries to give a joint vision on the financial aspects that they must be considered in the study of the managerial growth, realizing for it a brief synopsis of the theoretical evolution of the initial offer of Modigliani and Miller, centring specially the work on the fiscal aspects, as factor that can determine the managerial growth and the financial structure of the company.